Soft package lithium ion battery and preparation method thereof

By introducing the connection layer in the secondary seal area of ​​the soft -envelope lithium -ion battery and the cross -linking solidification, the problem of edge defects caused by electrolyte residues was solved, which significantly increased the insulation and border tension of the battery, which enhanced it. Safety performance.

CN119340567APending Publication Date: 2025-01-21BEIJING WELION NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411595951.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing soft-pack lithium-ion batteries have edge sealing defects due to electrolyte residues after secondary packaging, which affects the overall strength and safety performance of the battery.

Method used

In the secondary seal area of ​​the soft -envelope lithium -ion battery, the connection layer is introduced between the inner heat seal layer of the aluminum plastic film, and the cross -linking and solidization after the second seal is used to solve the residual lithium salt and enhance the sealing sealing Border strength.

Benefits of technology

Effectively avoid the edge defects caused by lithium salt crystalline particles, improve the inside -in -end resistance and border tensile force, and enhance the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340567A_ABST
    Figure CN119340567A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soft package lithium ion batteries, in particular to a soft package lithium ion battery and a preparation method thereof.The aluminum plastic film comprises an outer nylon layer, a middle aluminum foil layer and inner heat sealing layers, and in a secondary sealing area of the battery, the two inner heat sealing layers of the aluminum plastic film are crosslinked through a connecting layer. According to the soft package lithium ion battery provided by the invention, the connecting layer is additionally arranged, so that the upper-layer aluminum-plastic film and the lower-layer aluminum-plastic film can be tightly connected together, the edge sealing tension of the lithium ion battery is improved, the edge sealing effect of the lithium ion battery is improved, the insulation internal resistance of the lithium ion battery can be remarkably improved, and the safety performance of the lithium ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soft-pack lithium-ion batteries, and in particular to a soft-pack lithium-ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles, energy storage, 3C digital, drones and other fields in recent years due to their advantages such as small size, light weight and reusability. Lithium-ion batteries can be divided into soft-pack batteries and hard-pack batteries according to the packaging method. Hard-pack batteries generally refer to batteries that use hard shells such as aluminum shells and steel shells as the outer packaging of the battery cells. Soft-pack batteries generally refer to batteries that use soft materials such as aluminum-plastic film and plastic film as the outer packaging of the battery cells. Compared with the heavier aluminum shells and iron shells, the packaging part of soft-pack batteries accounts for a smaller proportion of the overall battery mass, which is more conducive to the preparation of high-energy-density lithium-ion batteries.

[0003] When preparing lithium-ion batteries, after the battery cells are assembled and the electrolyte is injected, they will be packaged once (one seal). After the packaging is completed, subsequent infiltration and formation will be carried out. After the formation is completed, the reserved air bags will be cut off and then a second packaging (second sealing) will be carried out. In order to ensure sufficient infiltration and electrical performance, soft-pack lithium-ion batteries are often over-injected. During the second packaging after injection, the electrolyte will be extracted and the extracted electrolyte will remain in the secondary edge sealing area. During heat sealing, the small molecule solvent in the electrolyte can evaporate quickly under high temperature conditions, but the lithium salt in the electrolyte cannot evaporate. It is converted into lithium salt crystalline particles under high temperature conditions and stays in the secondary edge sealing area. Lithium salt crystalline particles can easily cause defects in the bonding of the aluminum-plastic film, affecting the overall strength of the edge sealing, and there is a risk of leakage in the later stage. Summary of the invention

[0004] The purpose of the present invention is to solve the secondary edge sealing defect caused by electrolyte residue in the prior art, and to provide a soft-pack lithium-ion battery and a preparation method thereof.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a soft-pack lithium-ion battery, wherein the aluminum-plastic film comprises an outer nylon layer, an intermediate aluminum foil layer and an inner heat-sealing layer, wherein in the secondary sealing area of ​​the battery, the two inner heat-sealing layers of the aluminum-plastic film are cross-linked by a connecting layer.

[0006] The second aspect of the present invention provides a method for preparing the soft-pack lithium-ion battery according to the first aspect of the present invention, wherein the method comprises: introducing the preparation material of the connecting layer into the second sealing area, and cross-linking and curing after the second sealing.

[0007] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0008] 1) The soft-pack lithium-ion battery provided in the present invention has a connecting layer added between the inner heat-sealing layer of the upper aluminum-plastic film and the inner heat-sealing layer of the lower aluminum-plastic film in the secondary sealing area. The preparation material of the connecting layer can dissociate the lithium salt remaining between the upper aluminum-plastic film and the lower aluminum-plastic film in the secondary sealing area, thereby avoiding the edge sealing defects caused by the formation of crystalline particles by the lithium salt and reducing the corrosion of the lithium salt on the aluminum-plastic film, thereby significantly improving the insulation internal resistance and edge sealing tension; in addition, the preparation material of the connecting layer can also be cross-linked with the inner heat-sealing layer of the upper aluminum-plastic film and the inner heat-sealing layer of the lower aluminum-plastic film, respectively, thereby tightly connecting the upper aluminum-plastic film and the lower aluminum-plastic film together, which helps to further improve the edge sealing effect and improve the safety performance of the lithium-ion battery.

[0009] 2) The method for preparing a soft-pack lithium-ion battery provided in the present invention introduces the preparation material of the connecting layer into the secondary sealing area and performs cross-linking and curing after the secondary sealing. Compared with the conventional method for preparing a soft-pack lithium-ion battery, the modification is small and suitable for industrial operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 The optical magnified image (left) and SEM image (right) of the inner surface of the aluminum-plastic film after the edge seal is opened in Example 1.

[0011] Figure 2 These are the optical magnified image (left) and SEM image (right) of the inner surface of the aluminum-plastic film after the edge seal is opened in comparative example 1. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] A first aspect of the present invention provides a soft-pack lithium-ion battery, wherein the outer packaging of the battery is an aluminum-plastic film, the aluminum-plastic film comprises an outer nylon layer, an intermediate aluminum foil layer and an inner heat-sealing layer, wherein in the secondary sealing area of ​​the battery, the two inner heat-sealing layers of the aluminum-plastic film are cross-linked by a connecting layer.

[0014] In a preferred embodiment of the present invention, the inner heat-sealing layer and the connecting layer are self-crosslinked.

[0015] Among them, in the present invention, when the preparation material of the connection layer is introduced into the secondary sealing area by coating, it can cover the entire secondary sealing area, and can form a complete connection layer between the two inner heat-sealing layers of the aluminum-plastic film, so that the two inner heat-sealing layers of the aluminum-plastic film can be connected together by cross-linking of the connection layer. When the coating liquid contains a monomer for forming the preparation material, the monomer is polymerized under irradiation to form a connection layer, and is cross-linked with the inner heat-sealing layer at the same time.

[0016] In a preferred embodiment of the present invention, the material of the inner heat-sealing layer is selected from polyolefin polymers; further preferably, the polyolefin polymer is selected from one or more of polyethylene, polypropylene and polybutylene.

[0017] In a preferred embodiment of the present invention, the material for preparing the connecting layer is selected from at least one of a polymer containing polar and non-polar segment structures or a monomer containing polar and non-polar segment structures that forms the material for preparing the connecting layer. That is, in the present invention, the material for preparing the connecting layer can be a polymer or a monomer that forms the polymer.

[0018] In a preferred embodiment of the present invention, the non-polar segment structure in the polymer is an alkyl segment or a halogenated alkyl segment, and the polar structure segment is a segment containing at least one element of O, S, and N.

[0019] Among them, in the present invention, under the action of heating and electron beam irradiation, the alkyl segment or the halogenated alkyl segment can undergo a cross-linking reaction with the inner heat-sealing layer, thereby tightly connecting the aluminum-plastic film together. The polar segment can undergo a dissociation reaction with the lithium salt, thereby eliminating the defects caused by the crystallization of the lithium salt. Further preferably, the polymer contains an alkyl side chain.

[0020] In a preferred embodiment of the present invention, the carbon number of the alkyl segment in the alkyl segment or the halogenated alkyl segment may be 5-25, and the halogen in the halogenated alkyl segment may be chlorine and / or bromine.

[0021] In a preferred embodiment of the present invention, the polymer is selected from one or more of poly(meth)acrylate, polyether, polycarbonate, polysulfone, polyamide, polyurethane, polyisocyanurate, preferably one or more of poly(meth)acrylate, polyether, polyurethane, polyisocyanurate.

[0022] In a preferred embodiment of the present invention, the poly(meth)acrylate is selected from one or more of polybutyl(meth)acrylate, polyhexyl(meth)acrylate, polylauryl(meth)acrylate, polydodecyl(meth)acrylate, polytrifluoromethylacrylate, polyhexafluorobutylmethacrylate, polydibromopropyl(meth)acrylate, polytribromophenyl(meth)acrylate and polypentabromophenyl(meth)acrylate.

[0023] In a preferred embodiment of the present invention, the polyether is selected from glycidyl alkyl esters, for example, polyglycidyl hexadecyl ether.

[0024] In a preferred embodiment of the present invention, the polyurethane is selected from polyurethanes containing ≥6 carbon alkyl segments.

[0025] In a preferred embodiment of the present invention, the polyisocyanurate is selected from one or more of polyisocyanuric acid tris(2-acryloxyethyl ester), polyisocyanuric acid bis(2-acryloxyethyl ester), and polytriallyl isocyanurate.

[0026] Among them, in the present invention, too many non-segments will reduce the proportion of polar groups and be unfavorable for the dissociation of residual lithium salts, and too short segments are not conducive to crosslinking with the inner heat seal layer. The introduction of some urea rings is conducive to improving corrosion resistance and mechanical strength.

[0027] In a preferred embodiment of the present invention, the polar and non-polar segment structure monomers of the preparation material forming the connecting layer are selected from one or more of (meth)acrylate, glycerol ether, unsaturated carbonate, unsaturated sulfone, unsaturated amide, isocyanate and polyol composition, and unsaturated isocyanurate. Among them, in the present invention, taking (meth)acrylate as an example, (methyl) represents the selective presence of methyl, that is, (meth)acrylate can be methacrylate, acrylate, or methacrylate and acrylate.

[0028] In a preferred embodiment of the present invention, the (meth)acrylate is selected from one or more of butyl (meth)acrylate, hexyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, trifluoromethylacrylate, hexafluorobutyl methacrylate, dibromopropyl (meth)acrylate, tribromophenyl (meth)acrylate and pentabromophenyl (meth)acrylate.

[0029] In a preferred embodiment of the present invention, the glyceryl ether is selected from glycidyl hexadecyl ester.

[0030] In a preferred embodiment of the present invention, the unsaturated amide is selected from methacrylamide.

[0031] In a preferred embodiment of the present invention, in the isocyanate and polyol composition, the isocyanate is selected from isocyanates containing ≥6 carbon alkyl segments, more preferably hexamethylene diisocyanate; the polyol is selected from polyester polyols, preferably polyethylene glycol. Polyethylene glycol has a COC bond, which provides salt dissociation ability for polyurethane.

[0032] In a preferred embodiment of the present invention, the unsaturated isocyanurate is selected from one or more of tris(2-acryloxyethyl isocyanurate), bis(2-acryloxyethyl isocyanurate), and triallyl isocyanurate.

[0033] In a preferred embodiment of the present invention, the aluminum-plastic film further comprises a water and oxygen barrier layer, wherein the water and oxygen barrier layer is arranged on the outer nylon layer. In the present invention, the water and oxygen barrier layer can be an aluminum layer, a copper layer, a SiO2 coating, etc.

[0034] In a preferred embodiment of the present invention, the insulation internal resistance of the soft-pack lithium-ion battery is 700-1000 MΩ.

[0035] In a preferred embodiment of the present invention, the edge sealing tension of the second sealing area of ​​the soft-pack lithium-ion battery is 70-100 N / cm.

[0036] Among them, in the present invention, the edge sealing tension refers to the maximum tension required to tear the edge sealing apart; the greater the tension, the better the adhesion and fit between the aluminum-plastic films, and the lower the risk of leakage in the later stage.

[0037] The second aspect of the present invention provides a method for preparing the soft-pack lithium-ion battery of the first aspect of the present invention, wherein the method comprises: introducing the preparation material of the connecting layer into the second sealing area, and cross-linking and curing after the second sealing.

[0038] Among them, the conventional preparation method of soft-pack lithium-ion batteries known in the art includes lamination to form a winding core, tab welding, aluminum-plastic film punching, sealing, liquid injection, standing, formation and secondary sealing.

[0039] In a preferred embodiment of the present invention, the method of introducing the preparation material of the connecting layer into the second sealing area includes method I and / or method II; wherein, method I includes adding the preparation material containing the connecting layer into the electrolyte; and method II includes coating the coating liquid containing the preparation material of the connecting layer on the second sealing area.

[0040] Among them, in the present invention, when method I is adopted, the preparation material of the connecting layer can enter the second sealing area with the injection of the electrolyte, and under the action of the electron beam, it can be cross-linked with the aluminum-plastic film and the inner heat-sealing layer, and the inner heat-sealing layer and the residual area polymer / monomer itself can be internally cross-linked.

[0041] In the present invention, the material for preparing the connecting layer is selected as above (ie, the same as described in the first aspect of the present invention).

[0042] In a preferred embodiment of the present invention, the mass content of the material for preparing the connecting layer in the electrolyte is 1-10% of the total mass of the electrolyte. For example, the mass content of the material for preparing the connecting layer in the electrolyte can be 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 9%, 10% of the total mass of the electrolyte, and any number between these values, preferably 1-5%.

[0043] In a preferred embodiment of the present invention, in the method I, the preparation method of the soft-pack lithium-ion battery includes: lamination to make a winding core, ear welding, aluminum-plastic film punching, sealing, injecting an electrolyte containing a preparation material of the connecting layer, standing, forming, secondary sealing and cross-linking curing.

[0044] The difference between this method and the conventional preparation method of soft-pack lithium-ion batteries is that an electrolyte containing the preparation material of the connection layer described in the first aspect of the present invention is added during the injection, and an additional cross-linking and curing operation is performed after the second sealing. In addition, the remaining operations are the same as the conventional preparation method of soft-pack lithium-ion batteries, and the present invention will not repeat them one by one.

[0045] In a preferred embodiment of the present invention, in the method II, the solvent in the coating liquid is selected from one or more of ethyl methyl carbonate, propylene carbonate, dimethyl carbonate, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, and dimethylacetamide.

[0046] In a preferred embodiment of the present invention, in the method II, the coating liquid is applied with a dry thickness of 1-10 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, preferably 2-5 μm;

[0047] Among them, in the present invention, the coating dry thickness is also called coating thickness, which refers to the thickness of the coating layer formed after the coating liquid is dried. The greater the coating thickness, the greater the insulation internal resistance, but the corresponding edge sealing tension is smaller. When the coating thickness is within the above-defined range, the soft-pack lithium-ion battery can have both good insulation internal resistance and edge sealing tension.

[0048] In a preferred embodiment of the present invention, in the method II, the preparation method of the soft-pack lithium-ion battery includes: lamination to make a winding core, ear welding, aluminum-plastic film punching, sealing, liquid injection, standing, formation, coating the coating liquid in the second sealing area, drying, secondary sealing and cross-linking curing.

[0049] Compared with the conventional preparation method of soft-pack lithium-ion batteries, the difference between this method and the conventional preparation method of soft-pack lithium-ion batteries is that the coating liquid is applied to the second sealing area after formation and dried, and an additional cross-linking and curing operation is performed after the second sealing. Other than that, the remaining operations are the same as the conventional preparation method of uniform soft-pack lithium-ion batteries.

[0050] In a preferred embodiment of the present invention, in the method II, the preparation method of the soft-pack lithium-ion battery includes: modified aluminum-plastic film, lamination to make a winding core, pole ear welding, modified aluminum-plastic film punching, sealing, liquid injection, standing, formation, second sealing and cross-linking curing; wherein, the preparation method of the modified aluminum-plastic film includes: first coating a coating liquid containing a preparation material of the connecting layer on the second sealing area of ​​the aluminum-plastic film, and then drying to obtain a modified aluminum-plastic film.

[0051] Among them, in the present invention, the difference between this method and the conventional preparation method of soft-pack lithium-ion batteries is that before preparation, a coating liquid is pre-coated on the second sealing area of ​​the aluminum-plastic film and dried, and then the aluminum-plastic film modified with the coating liquid is assembled in the same manner as the conventional preparation method, except that an additional cross-linking and curing operation is performed after the second sealing.

[0052] In a preferred embodiment of the present invention, in the method II, the drying temperature is 80-120° C., and the drying time is 2-6 min.

[0053] In a preferred embodiment of the present invention, the cross-linking and curing operation includes heating first and then electron beam irradiation.

[0054] In a preferred embodiment of the present invention, the heating operating conditions include: the heating temperature is 100-200°C, preferably 130-170°C.

[0055] In a preferred embodiment of the present invention, the heating operation conditions further include: the heating time is 1-60s, preferably 2-10s.

[0056] In a preferred embodiment of the present invention, the operating conditions of the electron beam irradiation include: the electron beam energy is 100-300 eV, preferably 150-250 eV.

[0057] In a preferred embodiment of the present invention, the operating conditions of the electron beam irradiation further include: an irradiation dose of 100-300 kGy, preferably 150-250 kGy.

[0058] In a preferred embodiment of the present invention, the operating conditions of the electron beam irradiation further include: the irradiation time is 1-8s, preferably 1-5s.

[0059] Among them, in the present invention, under the dual effects of heating and electron beam irradiation, the preparation material of the connecting layer can, on the one hand, undergo a dissociation reaction with the lithium salt to avoid the formation of lithium salt crystalline particles; on the other hand, due to the cross-linking and bonding effects, the setting of the connecting layer helps to significantly improve the bonding effect.

[0060] The present invention will be described in detail below through examples.

[0061] The aluminum-plastic film is a three-layer composite film of nylon / aluminum / PP.

[0062] Preparation Example 1: The specific preparation method of poly dodecyl acrylate is as follows: 20g dodecyl acrylate (Inokai reagent platform, item number: A55365, purity 90%), 1g azobisisobutyronitrile, and 80g ethylene glycol dimethyl ether are added to a three-necked flask and stirred evenly, and then placed at 60°C for reaction for 10h, and the reactant is dried at 100°C for 10h to obtain poly dodecyl acrylate. The weight average molecular weight M is tested by GPC. w =146349 g / mol.

[0063] Preparation Example 2: The specific preparation method of polyurethane is as follows: 20g of a mixture of hexamethylene diisocyanate (Inokai reagent platform, item number: A88989, purity 99%) and polyethylene glycol (Inokai reagent platform, item number: A35872, Mn=2000) with a molar ratio of 2:1 is added to 80g of ethylene glycol dimethyl ether in a three-necked flask and stirred evenly, and then placed at 60°C for reaction for 10h, and the reactant is dried at 100°C for 10h to obtain polyurethane, and the weight average molecular weight M is tested by GPC. w =253864 g / mol.

[0064] Preparation Example 3: The specific preparation method of polyglycidyl hexadecyl ether is as follows: 20g of glycidyl hexadecyl ether (Inokai reagent platform, item number: G476805-10g, industrial grade) and 0.1g of lithium hexafluorophosphate are added to 80g of ethylene glycol dimethyl ether in a three-necked flask, stirred evenly, and then placed at 60°C for reaction for 24h, and the reactant is dried at 100°C for 10h to obtain polyglycidyl hexadecyl ether, and the weight average molecular weight M is tested by GPC. w =112368g / mol.

[0065] Example 1

[0066] 1) adding 10 g of the polylauryl acrylate prepared in Preparation Example 1 to 100 g of ethyl methyl carbonate, and stirring at 60° C. for 24 h to obtain a coating solution;

[0067] 2) applying the coating liquid to the secondary sealing area of ​​the soft-pack battery cell after the lamination, ear welding, aluminum-plastic film punching, sealing, liquid injection, standing and formation are completed in sequence, and drying is carried out at 100° C. for 2 minutes, and the coating dry thickness is 2 μm;

[0068] 3) Place the dried soft-packed battery cell in a secondary sealing machine and perform secondary sealing at 180°C for 5 seconds;

[0069] 4) The heat clamp with a heating function is heated to 150° C., and then the secondary edge sealing area of ​​the soft-pack battery cell that has completed the secondary packaging is heated. After heating at 150° C. for 3 seconds, it is placed in an electron beam device and cross-linked and cured under the conditions of an electron beam energy of 200 eV, an irradiation dose of 200 kGy, and an electron beam irradiation time of 2 seconds to obtain a soft-pack lithium-ion battery.

[0070] Example 2

[0071] Compared with Example 1, the difference is that in step 2), the above-mentioned coating liquid is applied to the secondary sealing area of ​​the soft-pack battery cell after the stacking and winding core making, the ear welding, the aluminum-plastic film punching, the sealing, the liquid injection, the standing and the formation are completed in sequence, the coating thickness is adjusted, and the coating is dried at 100°C for 2 minutes, and the dry coating thickness is 5μm.

[0072] Example 3

[0073] Compared with Example 1, the difference is that in step 2), the above-mentioned coating liquid is applied to the secondary sealing area of ​​the soft-pack battery cell after the stacking and winding core making, the ear welding, the aluminum-plastic film punching, the sealing, the liquid injection, the standing and the formation are completed in sequence, the coating thickness is adjusted, and the coating is dried at 100°C for 2 minutes, and the dry coating thickness is 10μm.

[0074] Example 4

[0075] Compared with Example 1, the difference is that in step 1), the mass of polylauryl acrylate is replaced by the polyurethane prepared in Preparation Example 2 of the same mass.

[0076] Example 5

[0077] Compared with Example 1, the difference is that in step 1), the mass of polylauryl acrylate is replaced by the same mass of polyglycidyl hexadecyl ether prepared in Preparation Example 3.

[0078] Example 6

[0079] 1) adding dodecyl acrylate monomer to an electrolyte (EC / EMC / DMC=1 / 1 / 1, 1MLiPF6, 2wt%VC), and stirring at room temperature for 5 hours; wherein the mass content of dodecyl acrylate in the electrolyte is 2%;

[0080] 2) injecting the electrolyte containing dodecyl acrylate into the battery cell which has completed the lamination and winding, the tab welding, the aluminum-plastic film punching and sealing in sequence, and after the injection, standing and forming, to obtain a soft-pack battery cell;

[0081] 3) placing the above soft-packed battery cell in a secondary sealing machine and performing secondary sealing at 180° C. for 5 seconds;

[0082] 4) The heat clamp with a heating function is heated to 150° C., and then the secondary edge sealing area of ​​the soft-pack battery cell that has completed the secondary packaging is heated. After heating at 150° C. for 3 seconds, it is placed in an electron beam device and cross-linked and cured under the conditions of an electron beam energy of 200 eV, an irradiation dose of 200 kGy, and an electron beam irradiation time of 2 seconds to obtain a soft-pack lithium-ion battery.

[0083] Example 7

[0084] The same as Example 6, except that the mass content of dodecyl acrylate in the electrolyte is 5wt%.

[0085] Example 8

[0086] The same as Example 6, except that the mass content of dodecyl acrylate in the electrolyte is 8wt%.

[0087] Comparative Example 1

[0088] The same as Example 1, except that the conventional preparation method is used to sequentially perform lamination to form a winding core, electrode ear welding, aluminum-plastic film punching, sealing, liquid injection, standing, formation, secondary sealing and capacity separation to obtain a soft-pack lithium-ion battery.

[0089] Comparative Example 2

[0090] The same as Example 1, except that no coating liquid is prepared to coat the secondary sealing area, and only the edge sealing is subjected to electron beam irradiation treatment.

[0091] Comparative Example 3

[0092] The same as Example 1, except that no electron beam irradiation is applied in step 4).

[0093] Comparative Example 4

[0094] The same as Example 6, except that no electron beam irradiation is applied in step 4).

[0095] Test Example 1

[0096] The insulation internal resistance of the soft-pack lithium-ion batteries prepared in Examples 1-8 and Comparative Examples 1-4 was tested using an insulation internal resistance tester (HIOKI ST5520 insulation resistance tester), and the test results are shown in Table 1. After the insulation internal resistance test, the soft-pack lithium-ion battery was disassembled, and the second sealing area was cut into 1.5 cm wide sample strips, and a 180° tensile test was performed using a tensile machine, and the step speed of the tensile machine was 50 mm / min.

[0097] Table 1

[0098]

[0099]

[0100] Among them, insulation internal resistance: insulation internal resistance represents the contact between the residual lithium salt and the upper and lower aluminum foils. The larger the insulation internal resistance, the less the lithium salt pierces the inner heat seal layer, and the lower the risk of corrosion to the aluminum foil in the later stage. Edge sealing tension: edge sealing tension is the maximum tension required to tear the edge sealing apart. The greater the tension, the better the adhesion and fit between the aluminum-plastic film, and the lower the risk of leakage in the later stage.

[0101] As shown in Table 1, the insulation internal resistance of the soft-pack lithium-ion battery prepared in the present invention is between 700-1000 MΩ, and the edge sealing tension of the second sealing area is between 70-100 N / cm, indicating that the soft-pack lithium-ion battery has excellent safety performance.

[0102] By comparing Examples 1-3, it can be seen that the greater the dry coating thickness, the greater the insulation internal resistance of the soft-pack lithium-ion battery, but the corresponding edge sealing tension is smaller. This is because, as the dry coating thickness increases, on the one hand, the amount of connecting layer material added can be increased, which helps to eliminate the defects caused by lithium salts, thereby improving the insulation internal resistance of the lithium-ion battery. But at the same time, if the dry coating thickness is too large, the overall packaging strength of the lithium-ion battery will be reduced. Therefore, within the range of the dry coating thickness defined by the present invention, the lithium-ion battery can have both high insulation internal resistance and high edge sealing strength.

[0103] The test results of Examples 1, 4 and 5 show that the insulation internal resistance and edge sealing tensile force of the soft-pack lithium-ion battery in Examples 1 and 5 are significantly greater than those in Example 4. This may be because polylauryl acrylate and glycidyl hexadecyl ether contain alkyl segments, which are more easily cross-linked during irradiation.

[0104] By comparing Examples 6-8, it can be seen that the more the mass content of the preparation material of the connecting layer in the electrolyte, the greater the insulation internal resistance of the soft-pack lithium-ion battery, but the corresponding edge sealing tension is smaller. When the mass content of the preparation material of the connecting layer in the electrolyte is within the range defined by the present invention, the soft-pack lithium-ion battery can have both good insulation internal resistance and edge sealing tension.

[0105] By comparing Example 1 and Comparative Example 1, it can be seen that in the present invention, under the dual effects of heating and electron beam irradiation, the preparation material of the connecting layer can, on the one hand, undergo a dissociation reaction with the lithium salt to avoid the formation of lithium salt crystal particles that pierce the heat sealing layer and can significantly increase the insulation internal resistance; on the other hand, the preparation material of the connecting layer can undergo a cross-linking reaction with the inner heat sealing layer to firmly connect the aluminum-plastic film together, thereby greatly increasing the edge sealing tension.

[0106] By comparing Example 1 and Comparative Example 2, it can be seen that although simple radiation cross-linking can improve the edge sealing tensile force to a certain extent, it cannot solve the problem of lithium salt piercing the heat sealing layer caused by residual electrolyte; and because high-temperature heating is required before irradiation, PP melts again, resulting in more serious defects caused by the electrolyte and a greater decrease in the overall insulation internal resistance.

[0107] By comparing Example 1 and Comparative Example 3, as well as Example 6 and Comparative Example 4, it can be seen that in the absence of electron beam irradiation, the adhesion strength between the polar coating and the non-polar PP layer of the aluminum-plastic film is poor, while after irradiation, the bonding with PP and the binding effect of the internal ionized salt are improved.

[0108] Test Example 2

[0109] After the tensile test of the soft-pack lithium-ion batteries prepared in Example 1 and Comparative Example 1 was completed, the inner surface of the aluminum-plastic film after tearing was subjected to optical magnification characterization and SEM characterization. The results are as follows: Figure 1 and 2 shown. Figure 1 and Figure 2 The left image is an optical magnification image, and the right image is a SEM image.

[0110] Among them, Figure 1 It can be seen from the optical magnification image in that the surface of the soft-pack lithium-ion battery prepared in Example 1 is smoother and flatter after the edge seal is torn off, and no obvious defects exist. Further magnification for SEM characterization shows that no microscopic crystalline particles are observed in the SEM image.

[0111] Depend on Figure 2 From the optical magnification image in, it can be seen that after the edge seal of the soft-pack lithium-ion battery prepared in Comparative Example 1 was torn open, there were many white defect areas on the surface. SEM magnification of the white defect area showed that some particles were aggregated in this area.

[0112] By comparison Figure 1 and Figure 2 It can be seen that the soft-pack lithium-ion battery prepared in Example 1 can solve the problem of lithium salt residue at the edge sealing, and reduce the safety hazard caused by leakage of the edge sealing in the later battery.

[0113] It can be seen from the SEM characterization results that the SEM characterization results of the soft-pack lithium-ion batteries prepared in Examples 2-8 are similar to the SEM characterization results of the soft-pack lithium-ion batteries prepared in Example 1.

[0114] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A soft-pack lithium-ion battery, wherein the outer packaging of the battery is an aluminum-plastic film, wherein the aluminum-plastic film comprises an outer nylon layer, an intermediate aluminum foil layer and an inner heat-sealing layer, characterized in that: In the secondary sealing area of ​​the battery, the two inner heat-sealing layers of the aluminum-plastic film are cross-linked through a connecting layer.

2. The battery according to claim 1, wherein The inner heat-sealing layer and the connecting layer are self-crosslinking.

3. The battery according to claim 1 or 2, wherein: The material of the inner heat-sealing layer is selected from polyolefin polymers; preferably, the polyolefin polymer is selected from one or more of polyethylene, polypropylene, and polybutylene.

4. The battery according to any one of claims 1 to 3, wherein: The material for preparing the connecting layer is selected from at least one of a polymer containing polar and non-polar segment structures or a monomer containing polar and non-polar segment structures that forms the material for preparing the connecting layer; Preferably, the non-polar segment structure is an alkyl segment or a halogenated alkyl segment, and the polar structure segment is a segment containing at least one element of O, S, and N; Preferably, the polymer is selected from one or more of poly(meth)acrylate, polyether, polycarbonate, polysulfone, polyamide, polyurethane, and polyisocyanurate; Preferably, the poly(meth)acrylate is selected from one or more of polybutyl(meth)acrylate, polyhexyl(meth)acrylate, polylauryl(meth)acrylate, polydodecyl(meth)acrylate, polytrifluoromethylacrylate, polyhexafluorobutylmethacrylate, polydibromopropyl(meth)acrylate, polytribromophenyl(meth)acrylate and polypentabromophenyl(meth)acrylate; Preferably, the polyether is selected from glycidyl alkyl esters; Preferably, the polyurethane is selected from polyurethanes containing ≥6 carbon alkyl segments; Preferably, the polyisocyanurate is selected from one or more of polyisocyanurate tris(2-acryloxyethyl) ester, polyisocyanurate bis(2-acryloxyethyl) ester, and polytriallyl isocyanurate.

5. The battery according to claim 4, wherein The monomers forming the material for preparing the connecting layer are selected from one or more of (meth)acrylate, glycerol ether, unsaturated carbonate, unsaturated sulfone, unsaturated amide, isocyanate and polyol composition, and unsaturated isocyanurate monomers; Preferably, the (meth)acrylate is selected from one or more of butyl (meth)acrylate, hexyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, trifluoromethylacrylate, hexafluorobutyl methacrylate, dibromopropyl (meth)acrylate, tribromophenyl (meth)acrylate, pentabromophenyl (meth)acrylate; Preferably, the glyceryl ether is selected from glycidyl hexadecyl ester; Preferably, the unsaturated amide is selected from methacrylamide; Preferably, in the isocyanate and polyol composition, the isocyanate is selected from isocyanates containing ≥6 carbon alkyl segments, more preferably hexamethylene diisocyanate; the polyol is selected from polyester polyols, preferably polyethylene glycol; Preferably, the unsaturated isocyanurate is selected from one or more of tris(2-acryloxyethyl isocyanurate), bis(2-acryloxyethyl isocyanurate), and triallyl isocyanurate.

6. A method for preparing a soft-pack lithium-ion battery according to any one of claims 1 to 5, characterized in that: The method comprises: introducing the preparation material of the connection layer into the second sealing area, and performing cross-linking and curing after the second sealing.

7. The preparation method according to claim 6, wherein: The method of introducing the preparation material of the connecting layer into the second sealing area includes method I and / or method II; wherein, method I includes adding the preparation material containing the connecting layer into the electrolyte; and method II includes coating the coating liquid containing the preparation material of the connecting layer on the second sealing area.

8. The preparation method according to claim 7, wherein: In the method I, the mass content of the material for preparing the connecting layer in the electrolyte is 1-10% of the electrolyte, preferably 1-5%; Preferably, in the method I, the preparation method of the soft-pack lithium-ion battery includes: lamination to make a winding core, ear welding, aluminum-plastic film punching, sealing, injecting an electrolyte containing a preparation material of the connecting layer, standing, forming, secondary sealing and cross-linking curing.

9. The preparation method according to claim 7, wherein: In the embodiment II, the coating thickness of the coating liquid is 1-10 μm, preferably 2-5 μm.

10. The preparation method according to claim 7, wherein: In the method II, the preparation method of the soft-pack lithium-ion battery includes: laminating and making a winding core, welding the tabs, punching holes in the aluminum-plastic film, sealing, injecting liquid, standing, forming, coating the second sealing area with a coating liquid, drying, secondary sealing and cross-linking and curing; Alternatively, in the method II, the preparation method of the soft-pack lithium-ion battery includes: modified aluminum-plastic film, lamination to make a winding core, pole ear welding, modified aluminum-plastic film punching, sealing, liquid injection, standing, chemical formation, second sealing and cross-linking curing; wherein, the preparation method of the modified aluminum-plastic film includes: first coating a coating liquid containing a preparation material of a connecting layer on the second sealing area of ​​the aluminum-plastic film, and then drying to obtain a modified aluminum-plastic film.

11. The preparation method according to claim 10, wherein: The drying temperature of the drying is 80-120° C., and the drying time is 2-6 minutes.

12. The preparation method according to any one of claims 6 to 11, wherein: The cross-linking and curing operation includes heating first and then electron beam irradiation; Preferably, the heating operating conditions include: the heating temperature is 100-200°C, preferably 130-170°C; Preferably, the heating time is 1-60s, preferably 2-10s; Preferably, the operating conditions of the electron beam irradiation include: the electron beam energy is 100-300 eV, preferably 150-250 eV; Preferably, the irradiation dose is 100-300 kGy, preferably 150-250 kGy; Preferably, the irradiation time is 1-8 s, preferably 1-5 s.